2012
DOI: 10.1038/onc.2012.458
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells promote growth and angiogenesis of tumors in mice

Abstract: Though the early integration of mesenchymal stem cells (MSCs) into tumor-associated stroma of cancer has been demonstrated, the functional contributions and underlying mechanisms of these cells to tumor growth and angiogenesis remain to be clarified. Using a xenograft model, human colorectal cancer cells, MSCs, and their cell mixture were introduced to a subcutaneous site of immunodeficient mice. The tumor growth rate and angiogenesis of each transplantation was then compared. We demonstrate that a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 29 publications
1
130
0
2
Order By: Relevance
“…Several studies demonstrated anti-tumor effects [8][9][10] whereas others showed tumor promoting effects [11][12][13] of MSCs in different tumor models. Regarding the effects on CRC, most of the studies have shown a pro-cancer effect of MSCs [29][30][31]. Consistently, we observed that trophic factors secreted by MSCs can promote colony formation and growth of a metastasis CRC cell line.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies demonstrated anti-tumor effects [8][9][10] whereas others showed tumor promoting effects [11][12][13] of MSCs in different tumor models. Regarding the effects on CRC, most of the studies have shown a pro-cancer effect of MSCs [29][30][31]. Consistently, we observed that trophic factors secreted by MSCs can promote colony formation and growth of a metastasis CRC cell line.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, ET-1 promotes growth, migration, contraction, and the production of ECMmodifying proteins in fibroblasts adjacent to colon cancer, suggesting a role of ET-1 in the formation of a supportive stroma (16). More recently, it has been shown that when colorectal cancer cells were mixed with nontumorigenic MSC, they secrete enhanced levels of ET-1, thereby increasing the capacities of EC for recruitment and angiogenesis, demonstrating a further integration of tumor-associated stroma with ET-1 signaling (12).…”
Section: Role Of Et-1 In the Interactions Of Tumor Cells With The Micmentioning
confidence: 99%
“…Although we did find encouraging data that QDloaded MSCs migrate toward breast tumor in vivo, it must be taken into account that MSCs could act as pro-tumorigenic due to paracrine stimulation that promotes metastases, angiogenesis, immune system suppression, expansion of cancer stem cells, [87][88][89] as well as tumor suppressor agents through the inhibition of migration, suppression of cell cycle, and apoptosis induction. [90][91][92] Thus, to prevent therapy-induced tumor progression, QDs ought to act as theranostic agents, combining diagnostics due to PL and therapeutics due to the attachment of anticancer agents, for example, photosensitizers.…”
mentioning
confidence: 95%